Applications of extracellular vesicles in tissue regeneration - Ma, Zhijie (Biomicrofluidics, 2020)
Extracellular vesicles (EVs) can be classified into several types based on their different biosyntheses or release pathways, including exosomes, microvesicles, apoptotic bodies, and large oncosomes. As they contain DNAs, RNAs, proteins, and other bioactive signals, EVs have been utilized in the diagnosis field for a long time. Considering the fact that stem cells have been widely used for tissue regeneration and EVs possess similar biological properties to their source cells, tissue regeneration abilities of EVs have recently attracted much attention in the regenerative medicine field. In this paper, recent advances and challenges of EVs applied in the repair and regeneration of damaged tissues, such as skin, heart, liver, kidney, bone, and central nervous system, have been summarized. Specifically, critical bioactive molecules, which are encapsulated within EVs and play significant roles in the tissue regeneration, have been highlighted. Finally, the prospects and future development directions of the application of EVs in the field of tissue regeneration have been discussed.